A judicialização da saúde no Rio Grande do Sul e o fornecimento de medicamentos: uma análise a partir da teoria das restrições - Brasil, Andréia Regina Blau (2022)
This research approaches the administrative procedures for the supply of medicines and the judicialization of health in Rio Grande do Sul, based on the theory of restrictions. It deals with the implementation of public health policy in the context of Public Administration in Brazil. To identify the restrictions, the process of identifying the bottlenecks of the Theory of Restrictions was adopted, which was used in the administrative procedure for requesting medication. This study aimed to identify the possible bottlenecks in the administrative procedures of the processes of judicialization of the pharmaceutical assistance policy of the State Department of Health of Rio Grande do Sul in the period from 2017 to 2020. search is the political constraint with 08 cases. Secondly, there are the capacity or physical restrictions and the behavioral restrictions with 07 events. Thirdly, there are logistical constraints, with 06 cases. In fourth place, material restrictions are observed, with 03 cases evidenced. Finally, financial restrictions were found in 02 cases, being them financial restrictions and blocking of executive values. It is concluded that the existing bottlenecks in the administrative procedures of the Pharmaceutical Assistance Policy, of the State Health Department of Rio Grande do Sul, which result in lawsuits are: prescriptions of medicines outside the SUS list, prescription of medicines for CIDS, which are not included in the protocol, referral of administrative processes with lack of documents or examination, prescribed medication that does not fit the protocol for receiving the medication due to the result of the exams evaluated by the expert, and also after the administrative approval, there are shortages of stock of drugs that lead to lawsuits. It is noted that the restrictions in the administrative flows of the interference of the judicialization of medicines in the cycle of Pharmaceutical Assistance were more evident than in the actualization of the right to access to medicines, determined in the national legislation.